Quantitative Detection of Zinc Oxide Nanoparticle in Environmental Water by Cloud Point Extraction Combined ICP-MS - Yuan Yang; Xin Liu; Lin Luo; Wenjing Wei; Qiang Wang; Jiachao Zhang (Adsorption Science & Technology)
The increasing usage of zinc oxide nanoparticles (ZnONPs) inevitably leads to their release into the environment. To understand their fate and toxicity in water systems, a reliable method for the quantitative analysis of ZnONPs in environmental waters is urgently needed to be established. In this study, a quantitative analytical method of ZnONPs in environmental waters was developed by cloud point extraction (CPE) combined inductively coupled plasma mass spectrometry (ICP-MS). To obtain high recoveries of ZnONPs, the CPE parameters including pH, surfactant concentration, salt concentration, bath temperature, and time were optimized. The results demonstrated that the addition of β-mercaptoethylamine could significantly reduce the interference of Zn2+ on the extraction of ZnONPs, while the CPE approach was not affected significantly by the typical environmental inorganic ion and ENMs (such as Au, TiO2, and Al2O3). The extraction method of ZnONPs with different diameters was also assessed, and satisfactory extraction efficiency was obtained. The results of ZnONP concentration in collected environmental water were in the range of 0.2±0.009-8.2±1.8 μg/L. And the recoveries of ZnONPs in different environmental waters were 62.2±2.0-88.1±9.6% at low concentration spiked levels (12.57-54.68 μg/L), demonstrating that it is efficient to extract trace ZnONPs from real environmental waters. This established method offered a reliable method for the quantitative determination of ZnONPs in environmental waters, which could further promote the study of the environmental behavior, fate, and toxicity of ZnONPs in an aqueous environment.